Medición y evaluación en comunicación estratégica. Estudio de caso proyecto Recypet de la empresa Enkador. - Salazar Cisneros, María Augusta (2014)
This work has as title "Strategic Communication Planning", and its general objective is to demonstrate through a case study (2012), that strategic communication planning, including the measurement function and evaluation of results, allow to determine the contribution of the communication management to organizational objectives. This study was maked at the company Enkador, and it was based in its proyect “Business Unit Recypet”. Enkador is dedicated to the manufacture of synthetic filaments for the textile industry, the establishment of recycling centers for plastic PET, and thermoplastics recycling plant operation. For this work was necesary a descriptive exploratory investigation. And it consists in the application of the evaluation model "Communication Management Bridge" using techniques of document analysis and semi-structured interviews. The results were qualitative type and have revealed that there is a direct contribution of communication management to Enkador’s objectives, that these contributions are not sufficient to achieve the organizational objectives; Recypet does not have a own strategic planning in managing communication; and its success depend of the ecuadorian idiosyncrasy.